Studies on GaN based HEMT heterostructures on 100-mm silicon grown by molecular beam epitaxy - Ravikiran Lingaparthi (2015)
GaN based high electron mobility transistors (HEMTs) have attracted great attention over the last two decades for the high power and high frequency applications due to their advantages of polarization induced high electron density, high break down field and high saturation electron velocity. Development of GaN based HEMT technology on heterogeneous substrates such as SiC, sapphire and silicon is necessary due to the lack of large diameter native substrates. Low cost, excellent quality, large area availability and the unique-possibility of integrating GaN based devices with well-established silicon electronics makes silicon the substrate of choice. However, large thermal coefficient mismatch (52%) and lattice constant mismatch (17%) of GaN with Si lead to poor crystalline quality and cracking of epitaxial layers. Thus, the main challenge is to grow crack-free, thick and high quality GaN buffers for GaN based HEMT heterostructures on large diameter Si substrate. This dissertation focuses on the growth and optimization of AlGaN/GaN HEMT heterostructures on 100-mm Si(111) substrate using ammonia-MBE growth process. Further, the feasibility of the growth of InAlN/GaN HEMT heterostructures on Si substrate using MBE growth technique has also been explored. Using ammonia-MBE growth process, AlN nucleation on the Si substrate was optimized to achieve lower roughness and good crystal quality 1st AlN layer. GaN buffer of 1000 nm thickness grown on the optimized 100 nm thick AlN showed heavy cracking. In order to produce crack free GaN buffers, AlGaN SML and AlN/GaN SMLs were studied. AlN/GaN SMLs stack was successful in achieving compressive stress, lower pit density, larger grain sizes and lower TDD in the GaN buffer compared to AlGaN SML. Hence, AlN/GaN SMLs were chosen for the development of AlGaN/GaN HEMT heterostructure growth on 100-mm Si substrate. A typical heterostructure with AlN/GaN SMLs consists of 50 nm of 1st AlN followed by the growth of 1st GaN/2nd AlN-SMLs. The 2nd GaN buffer was grown on top of the SMLs. Heterostructures grown using AlN/GaN SMLs intrinsically contain buried cracks in them. Using in-situ curvature measurements, different stages of buried crack formation such as the crack initialization and growth of strain free 2nd AlN followed by the lateral overgrowth of the cracked AlN were identified. Increased relaxation of 1st GaN with thickness was found to enhance the buried crack density. Moreover, the residual compression in 1st GaN together with the buried cracks in the heterostructure were found to act as a stress compensating mechanism to mitigate the stress from GaN to Si substrate. Thus, it is identified that AlN/GaN SMLs stack not only helps in inducing higher compression during the growth of 2nd GaN but also mitigates the stress from 2nd GaN to Si substrate during cool down. Using AlN/GaN SMLs, crack free AlGaN/GaN HEMT heterostructures with 2nd GaN up to 1000 nm thickness has been achieved on 100-mm Si substrate. AlGaN/GaN HEMT heterostructures grown using AlN/GaN SMLs showed a room temperature mobility of 1340 cm2/V.s and carrier concentration of 1.13 x 1013 cm-2, which resulted in a sheet resistance of 409 Ω/sq. Good uniformity is achieved in sheet resistance, sheet carrier concentration and mobility with their standard deviation values of 2.5, 0.6 and 2.6%, respectively, across 100-mm wafers. Even though crack free AlGaN/GaN HEMT heterostructures were achieved using AlN/GaN SMLs with 2nd GaN thickness of 1000 nm, the obtained wafer was tensile bowed in the range of 30-70 µm on 100-mm Si substrate. In order to achieve nearly flat bows, a new stack of AlGaN/AlN/GaN SMLs were studied. From in-situ stress measurements, the 2nd GaN was observed to be relaxed more for the heterostructures grown using AlGaN/AlN/GaN SMLs compared to AlN/GaN SMLs. However, the wafer bow was very compressive (+82 µm) for the heterostructures grown using AlGaN/AlN/GaN SMLs, while AlN/GaN SMLs produced tensile bow (-35 µm). Increased relaxation of 2nd GaN with high compressive bow indicates that the stress mitigation from GaN to Si is higher for the heterostructure grown using AlGaN/AlN/GaN SMLs compared to AlN/GaN SMLs. Using cross sectional transmission electron microscope (TEM) analysis, bending and looping of dislocation at AlGaN/2nd AlN and AlGaN/2nd GaN interfaces was attributed to the high relaxation of 2nd GaN. Weak beam dark field images showed extra tilt in the crystallites at AlGaN/2nd GaN interface, which was attributed to the increased stress mitigation and compressive bowing of the wafer. By increasing the 2nd GaN thickness up to 1400 nm, the compressive bowing of the wafer achieved was < +35 µm for the heterostructures using AlGaN/AlN/GaN SMLs. AlGaN/GaN HEMT heterostructures grown using this structure showed a room temperature sheet carrier concentration of 0.88 × 1013 cm-2 and mobility of 1380 cm2/V.s, which resulted in a sheet resistance of 517 Ω/sq. Moreover, the 2DEG electrical properties across the 100-mm wafer were observed to be uniform. Good 2DEG characteristics and control over the bowing of the AlGaN/GaN HEMT heterostructures on 100-mm Si substrate have been achieved. However, for various HEMT heterostructures, grown using both AlN/GaN SMLs and AlGaN/AlN/GaN SMLs, an average horizontal leakage current (HLC) of ~ 1×10-3 A/mm and a vertical leakage current (VLC) of ~ 1×10-1 A/cm2 were obtained at 20V. Oxygen was identified as the dominant impurity in the grown HEMT heterostructures from systematic SIMS and PL measurements. In addition, a parallel conduction channel was identified in the GaN buffer at the interface of 2nd AlN and 2nd GaN. To increase the buffer resistance, GaN buffer was carbon doped using CBr4 source during the growth. Two and one orders of reduction in the HLC and VLC were observed, respectively for the GaN buffer doped with the maximum available CBr4 BEP of 1.86× 10-7 mTorr in our system. AlGaN/GaN HEMT heterostructures grown using the carbon doped GaN buffer with 200 nm thick undoped GaN near the channel exhibited good 2DEG characteristics and reduction in the buffer leakage current by two orders of magnitude. To improve the confinement of 2DEG in AlGaN/GaN HEMT heterostructures, AlGaN/GaN/AlGaN double heterojunction HEMT (DH-HEMT) heterostructures were grown and investigated. Hall measurements on DH-HEMT structures showed a room temperature mobility of 1510 cm2/V.s with a sheet carrier concentration of 0.97 × 1013 cm-2. Capacitance-voltage measurements showed improved confinement of 2DEG for the DH-HEMT heterostructure, which helped in the enhancement of room temperature mobility. Further, it is observed that both SH- and DH-HEMT heterostructures show similar current driving capabilities. However, DH-HEMT shows 3 times higher buffer break down voltage compared to SH-HEMT. Having optimized the AlGaN/GaN HEMT heterostructures on Si (111) substrate, further efforts were made to achieve strain free lattice matched InAlN barrier growth for GaN based HEMT heterostructures. A combination of ammonia-MBE and PA-MBE growth processes was explored, where the GaN buffer was grown by ammonia-MBE while PA-MBE was used for low temperature InAlN barrier growth. InAlN/AlN/GaN HEMT heterostructure with indium composition of 24% was grown. Room temperature Hall measurement showed a carrier concentration of 7.3 × 1012 cm-2 and mobility of 140 cm2/V.s. However, post growth annealing of InAlN/AlN/GaN HEMT heterostructures showed a room temperature carrier concentration of 1.85 × 1013 cm-2 and mobility of 512 cm2/V.s. This improvement in the 2DEG properties is attributed to the improvement in the crystal quality of InAlN barrier due to annealing process. Thus, InAlN/AlN/GaN HEMT heterostructures with reasonable 2DEG characteristics have been demonstrated for the first time on Si substrate using a combination of ammonia-MBE and PA-MBE growth processes.